Decoding Mistakes: An Insightful Study on Students’ Errors in Writing Recount Texts - Arsjad, Rahmayanti A; Wahab, Isnaeni; Tanasy, Novalia; Zul Astri (English Language, Linguistics, and Culture International Journal, 2024)
This study aimed to determine the types of errors found in writing recount texts at SMA Negeri 3 Pangkep and to identify the most frequently occurring errors when students write recount texts at SMA Negeri 3 Pangkep. The researchers used a mixed-method approach, consisting of both qualitative and quantitative methods. The population in this study comprised class XI students, which consisted of six classes: XI IPA 1 (32 students), XI IPA 2 (31 students), XI IPA 3 (32 students), XI IPA 4 (30 students), XI IPS 1 (35 students), and XI IPS 2 (32 students). The total number of students was 192. Sampling was done using a purposive sampling technique, and the sample in this study was students from class XI IPA 1, consisting of 32 students. The results of this study, referring to the classification by Betty S. Azar, showed that the total number of errors was 370. The two most frequent types of errors were verb tense errors, with 73 errors (16% of the total), followed by word choice errors, with 38 errors (13.9% of the total).